Effective Removal of Gordon–Haus Jitter in Mode-Locked Fiber Lasers - Peng Qin; Sijia Wang; Minglie Hu; Youjian Song (IEEE Photonics Journal)
We demonstrate the effective removal of Gordon–Haus (GH) jitter in mode-locked fiber lasers based on the narrow bandpass filtering, verified from large positive dispersion to large negative dispersion. Simulations and experiments indicate that there exists an optimum filtering bandwidth for the near-zero GH jitter along with the constant directly coupled jitter. The corresponding measured root-mean-square timing jitter (10 kHz to 10 MHz) is restrained within 0.6 dB, even though the net dispersion is largely varied by 70% of the intracavity fiber dispersion. The demonstrated effective GH jitter elimination free of the dispersion management gives an easy way for the low-jitter laser design and the related high-precision applications outside the laboratory.